The Role of Adverse Childhood Experience on Adult Perceived Stress - Hindriasari, Lintang Pambayun; Rahapsari, Satwika; Yuniarti, Kwartarini Wahyu (Faculty of Psychology, Universitas Gadjah Mada, 2026)
There are some inconsistencies in previous studies regarding the relation between adverse childhood experiences and perceived stress. On the other hand, some studies have found that adverse childhood experiences affect the body's stress-related brain regions, such as the amygdala and prefrontal cortex. This research aims to re-examine the role of adverse childhood experiences (ACEs) in later perceived stress during the young adult phase. In total, 270 collegians (18-25 years old) in Yogyakarta completed the ACE-IQ and PSS-10 questionnaires. Data were analyzed using simple linear regression. The result indicates that adverse childhood experiences play a significant role in perceived stress in young adulthood (β = 20.5%, p < 0.001). Moreover, these predictions are signiﬁcant to both males and females. Despite these findings, the severity and profundity of the effect of ACEs were not quantitatively assessed. This highlights the need for subsequent research that provides more rigorous, detailed measurements of these variables. This research suggests early intervention for individuals with adverse childhood experiences to strengthen the protective factors against stress in adulthood.